CLASSIFICATION OF CORROSION PROCESSES - Rayimov Zukhriddin Khayriddin ugli; Jalilov Shokhabbos Oktamovich (American Journals, 2023)
In the chemical industry, the corrosion process occurring in technological devices is one of the urgent problems. Because corrosion causes great economic damage due to the rapid failure of metal products, equipment, structures and devices. This scientific article presents the classification of the corrosion process according to various symptoms.
Keywords: Chemical corrosion, gas corrosion, electrochemical corrosion, local corrosion, subsurface corrosion, pitting corrosion, сavitation corrosion.